Parameterization of a hydrologic model with geophysical data to simulate observed subsurface return flow paths - Claes, N. (2020)
We assessed four model structures each with three soil types of homogeneous hydrologic properties, two of which were evaluated with and without an anisotropy factor. Wetting front arrival times, derived from time‐lapse electrical resistivity measurements during flood irrigation field experiments, were used to evaluate the different representations of soil profile structures. These data indicated both vertical and lateral preferential flow in the subsurface during flood irrigation. Inclusion of anisotropy in the saturated hydraulic conductivity field improved the ability to model subsurface hydrologic behavior when flow processes shifted from uniform to heterogeneous flow, as occurs with lateral subsurface return flow under flood irrigation driven by a large pressure gradient. This reduced the need for detailed spatial discretization to represent these observed subsurface flow processes. The resulting simple three‐layer model structure was better able to model both the vertical and lateral flow processes than a more complex geospatial structure, suggesting that overinterpretation of smoothed inverted profiles could lead to misrepresentation of the subsurface structure.